Sport and Physical Activity in Corona Virus Isolation - Nikola Mijuskovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
The basic goal was presenting of sport in the time of the Covid 19 as a predominantly psychological struggle in which a competitor or recreational athlete is forced to beat himself. In addition, the goal is to put focus on the positive sides of the overall situation because the pandemic is a time when we can learn significant lessons that could be successfully applied at regular times. According to this, purpose of work was to spread awareness that each problem has its developmental aspects that we are obliged to notice and use. The method that lies behind the work is the observation of the behavior of the general population through their daily contacts with the challenges from the domain of isolation.